KUALITAS PELAYANAN FARMASI BERDASARKAN WAKTU PENYELESAIAN RESEP DI RUMAH SAKIT - Rusdiana, Nita; Wijayanti, Rahayu; Wahyuni, Sri (Universitas Ahmad Dahlan, 2015)
Based on Standard of Pharmaceutical Quality in Hospitals, there are methods are applied to distribute pharmaceuticals. One outpatient care efforts is to obtain medication prescribed by a doctor in a short time. The quality of outpatient pharmacy services as measured by the time of complete prescription at the pharmacy installation hospitals are based on reliability, responsiveness, assurance, empathy and tangibles. The study use cross-sectionalâs method, which is done by January-February in 2015, to analyze pharmacy quality standard and time of complete prescription. The data used in this study are primary data. This study was used sample of 157 respondents for quetioners and 787 outpatients prescriptions. The results showed that the highest satisfaction turn around time is 13 minutes. For the five variables tested showed that the responsiveness had the highest scores of 3.18 and tangibles has the lowest score of 2,53. Conclusion, time of complete prescription less than 13 minutes and supported by quetioners shows the highest variables of responsiveness at 3,29 are agreed that time to wait is not too long.